2009
DOI: 10.1007/s12369-009-0032-4
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Robust Speech Interface for Improved Human-Robot Interaction

Abstract: Robotics technology has made progress on a number of important issues in the last decade. However many challenges remain when it comes to the development of systems for human-robot interaction. This paper presents a case study featuring a robust dialogue interface for humanrobot communication onboard an intelligent wheelchair. Underlying this interface is a sophisticated software architecture which allows the chair to perform real-time, robust tracking of the dialogue state, as well as select appropriate respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…Various robots have previously been used to shape child behavior [16,3,5]. Robins et al [16] found that four children with ASD imitated a doll-like robotic toy, often without any initial prompting; they attributed this to the robot's "simpler" physical appearance.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Various robots have previously been used to shape child behavior [16,3,5]. Robins et al [16] found that four children with ASD imitated a doll-like robotic toy, often without any initial prompting; they attributed this to the robot's "simpler" physical appearance.…”
Section: Related Workmentioning
confidence: 99%
“…Duquette et al [3] found that a humanoid robot elicited more shared attention between two children with ASD than a human mediator. Ferrari et al [5] presented the IROMEC robot as a social mediator in interactive play between a child with ASD and a parent, teacher or therapist. Our work extends previous work by Feil-Seifer and Matarić, which introduced the use of graded cueing applied to socially assistive robots interacting with children with ASD [4].…”
Section: Related Workmentioning
confidence: 99%
“…To allow the user to make maximal use of these capabilities, it is important that the navigational targets be easy to select for users with a wide range of motion impairments. The smart wheelchair's onboard computer system is equipped with standard robotic software (mapping, localization, path planning and obstacle avoidance, see [11] for details) allowing it to reach the selected targets.…”
Section: Smartwheeler Projectmentioning
confidence: 99%
“…For one, robotic systems that use natural language for robot instruction either do not have natural language fully integrated into the robotic architecture (for example, Michalowski et al [2007]) or are limited to simple instructions (for example, Firby [1989], Atrash et al [2009]). And many systems use rule-based grammars due to the difficulty of producing a well-trained grammar on what is invariably the small amount of data applicable to the domain.…”
Section: Previous Workmentioning
confidence: 99%